2018
DOI: 10.7251/afts.2018.1019.065s
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency in Urban Areas by Innovative Permacultural Design

Abstract: First two paramount problems of the world are food security and energy. Permaculture isa new interdisciplinary branch of the science, which has positive synergistic effects and solves bothproblems, including environmental care. The paper analyzed the holistic principles of permaculturedesign and possible application in the flats, gardens in the suburbs and/or in the countryside, the urbanland, fields and plots, on rural estates and cottages, in commercial and industrial applications, as well asin educational i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Analysis of foreign ecological-psychological concepts showed that the quality and intensity of the impact of space on a person provides adaptive adjustment of his nervous networks, that is, experience of interaction with the environment determines the direction of his personality development [17,18,19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of foreign ecological-psychological concepts showed that the quality and intensity of the impact of space on a person provides adaptive adjustment of his nervous networks, that is, experience of interaction with the environment determines the direction of his personality development [17,18,19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have discussed the importance of ethical business practices and marketplace ethics in fostering consumer trust and loyalty. (14,16) Businesses that demonstrate integrity, honesty, and social responsibility are more likely to attract conscientious consumers and build long-term relationships.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Urban gardening, in several studies, indicates the potential advantages for the energy efficiency of existing buildings [47,48]. Urban gardening, such as rooftop gardens, have an insulation barrier to keep buildings warmer in the winter; meanwhile, their evapotranspiration effect, shades, and higher albedo value from the leaves could behave as a cooling structure in the summertime [21,49].…”
Section: Energy Conservation For Building Architectsmentioning
confidence: 99%